2004
DOI: 10.1093/ansci/82.2.459
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian follicular development in cattle selected for twin ovulations and births12

Abstract: Comparisons of numbers of antral ovarian follicles and corpora lutea (CL), of blood hormone concentrations, and of follicular fluid steroid concentrations and IGFBP activity were conducted between cows selected (twinner) and unselected (control) for twin births to elucidate genetic differences in the regulation of ovarian follicular development. Ovarian follicular development was synchronized among cows by a single i.m. injection of PGF2alpha on d 18 of the estrous cycle; six cows per population were slaughter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 33 publications
3
47
1
3
Order By: Relevance
“…Long-term selection for dizygotic twin births in this herd has increased twinning rate to an annual frequency of 50 to 55% (Echternkamp and Gregory 2002). These researchers (Echternkamp et al 2004) suggested that since IGF-I stimulates proliferation, differentiation, and steroidogenesis and inhibits apoptosis in ovarian follicular cells, more follicular cells are available with an increased frequency of ovulation and fertilization of two oocytes at approximately the same time. Australian researchers have reported positive phenotypic and genetic correlations (r p = 0.60; r g = 0.41) between IGF-I in the blood plasma of 6520 seedstock Angus beef cattle and RFI .…”
Section: Pregnancy Calving Twinning and Weaning Rates Of Damsmentioning
confidence: 97%
See 1 more Smart Citation
“…Long-term selection for dizygotic twin births in this herd has increased twinning rate to an annual frequency of 50 to 55% (Echternkamp and Gregory 2002). These researchers (Echternkamp et al 2004) suggested that since IGF-I stimulates proliferation, differentiation, and steroidogenesis and inhibits apoptosis in ovarian follicular cells, more follicular cells are available with an increased frequency of ovulation and fertilization of two oocytes at approximately the same time. Australian researchers have reported positive phenotypic and genetic correlations (r p = 0.60; r g = 0.41) between IGF-I in the blood plasma of 6520 seedstock Angus beef cattle and RFI .…”
Section: Pregnancy Calving Twinning and Weaning Rates Of Damsmentioning
confidence: 97%
“…Cows that produced HIGH RFI progeny also had nearly double the rate of calf death loss (8.06 vs. 4.24 vs. 4.02%, P = 0.10) and a trend (P = 0.10) toward less calving difficulty, likely due to the lighter birth weight of twins. The physiological basis for this observation is uncertain, though higher blood and follicular fluid concentrations of insulinlike growth factor-I (IGF-I) have been observed in the MARC research herd selected for the production of twins (Echternkamp et al 2004). Long-term selection for dizygotic twin births in this herd has increased twinning rate to an annual frequency of 50 to 55% (Echternkamp and Gregory 2002).…”
Section: Pregnancy Calving Twinning and Weaning Rates Of Damsmentioning
confidence: 99%
“…Cows with higher plasma IGF-I at the first and third week postpartum tended to have a shorter interval to first ovulation after calving [9] . Concentration of IGF-I is two-fold greater in blood and follicular fluid of twinner cows [39] . Therefore, the regulatory system of ovarian folliculogenesis to enable: the activation and development of more preantral follicles, the maintenance of larger pools of small antral follicles, the recruitment of more follicles within the cohort of developing follicles, and the selection of two or more dominant follicles within a follicular wave [30] .…”
Section: Discussionmentioning
confidence: 90%
“…Compared with ovaries from unselected cattle, ovaries from the twinner population have more microscopic secondary follicles (Cushman et al, 2000) and more small (≥ 5 mm), medium (5.1 to 9.9 mm) and large (≥ 1.0 mm) surface follicles (Echternkamp et al, 2004). In twinner cattle, the heritability of ovulation rate is 0.35 and there is a high genetic correlation (0.75) between ovulation rate and twinning rate (Gregory et al, 1997); therefore, one can theoretically use routine ultrasound evaluation to select females that produce more follicles, more oocytes and more embryos in assisted reproduction programs (Figure 5;De Roover et al, 2005).…”
Section: Evidence That Number Of Preovulatory Follicles Is Repeatablementioning
confidence: 96%